Efficacy and safety of the first domestic pegilated interferon alpha-2b «Pegaltevir» at chronic hepatitis C: pilot data of phase III clinical study - V. T. Ivashkin; Ye. N. Bessonova; P. O. Bogomolov; N. I. Geyvandova; K. V. Zhdanov; M. V. Mayevskaya; V. G. Morozov; V. D. Pasechnikov; I. Yu. Khomenko; A. V. Yagoda (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Comparative assessment of efficacy and safety of Pegaltevir and PegIntron in within pattern of combined antiviral therapy in previously untreated patients with chronic hepatitis C.Material and methods. Overall 140 patients with chronic hepatitis C, who received no antiviral therapy previously were included in original study. Patients were randomized in 4 groups. Groups differed in relation to received drug and hepatitis C virus genotype. All patients received 1,5 mkg per 1 kg body weight per week of Pegaltevir or PegIntron and 800–1400 mg of ribavirin per day. Preliminary estimation of drug efficacy was based on rates of rapid and early virologic response (RVR and EVR) achievement, dynamics of biochemical tests, dynamics of blood level of peginterferon alpha and neopterin. Safety features were estimated as well.Results. Comparative analysis has demonstrated absence of statistically significant distinctions of RVR and РВО rates at application of two peginterferon alpha-2b drugs. There were no differences in frequency of achievement of serologic response, as well as safety in Pegaltevir and PegIntron groups. Dynamics of blood concentration of peginterferon alpha correlated to neopterin concentration both in Pegaltevir group and in PegIntron group.Conclusions. Study results have shown high rates of RVR and РВО achievement, and acceptable safety profile of Pegaltevir, comparable with that of PegIntron at chronic hepatitis C in previously untreated patients.